Traumatic irreducible dislocation of the fifth metatarsophalangeal joint in pediatrics: case report and clinical experience - Wen Chao Li; Li Liu; Hui Chen; Zhen Dong Wang; Hui Xia Zhou (Frontiers Media S.A., 2024)
Dislocation of the metatarsophalangeal joint (MTPJ) by trauma commonly occurs in adults. Most dislocations of the MTPJ could be reduced by closed reduction. However, isolated traumatic irreducible dislocation of the fifth MTPJ is an extremely rare injury, particularly in children. We report the case of a 10-year-old boy with irreducible dislocation of the fifth MTPJ who presented with a dorsiflexion injury of the right foot 1 year previously. Closed reduction was attempted but failed. Computed tomography showed the dorsolateral dislocation of the fifth MTPJ. We performed an open reduction and metatarsal bone osteotomy, with a short osteotomy at approximately 0.8 cm. The osteotomy was adjusted to a reduction of the MTPJ and fixation by a lock compression plate. The distal growth plate in the metatarsal bone was protected to avoid pre-closure of the growth plate. There were no instances of dislocation or signs of avascular necrosis of the head of the metatarsal bone. The results of this study demonstrated that open reduction and metatarsal bone osteotomy could be an optional treatment for irreducible dislocation of the fifth MTPJ in children. We should pay more attention to the distal growth plate in the metatarsal bone to avoid pre-closure of the growth plate.